Goodbye, Antoura - Banean, Gaṛnik, 1910-1989 (My University, 2015)
This memoir offers the extraordinary story of what Karnig Panian endured in those years-as his people were deported from their Armenian community, as his family died in a refugee camp in the deserts of Syria, as he survived hunger and mistreatment in the orphanage. The Antoura orphanage was another project of the Armenian genocide: its administrators, some benign and some cruel, sought to transform the children into Turks by changing their Armenian names, forcing them to speak Turkish, and erasing their history. Panian's memoir is a full-throated story of loss, resistance, and survival, but told without bitterness or sentimentality. He paints a painfully rich and detailed picture of the lives and agency of Armenian orphans during the darkest days of World War I
A memoir of the Armenian genocide
Karnig Panian ; foreword by Vartan Gregorian ; translated by Simon Beugekian ; edited by Aram Goudsouzian ; introduction and afterword by Keith David Watenpaugh. - Stanford, CA : Stanford University Press, 2015. - xviii, 191 p. : ill., map ; 23 cm.
Տվյալները՝ ինտերնետային կայքից
https://www.pdfdrive.com/goodbye-antoura-a-memoir-of-the-armenian-genocide-d181898032.html
Childhood-Deportation-The desert-The orphanage at Hama-The orphanage at Antoura-The raids-The caves-Goodbye, Antoura-Sons of a great nation
Keywords: Banean, Gaṛnik, 1910-1989-Childhood and youth; Armenian Genocide, 1915-1923-Personal narratives; Orphans-Lebanon-Aynṭūrah-Biography; Armenian massacres survivors-Lebanon-Biography; World War, 1914-1918-Atrocities-Turkey; Armenian Genocide, 1915-1923